2015
DOI: 10.3109/23744235.2015.1055587
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections after abdominal surgery: incidence and risk factors. A prospective cohort study

Abstract: The significant risk factors defined should be addressed preoperatively to decrease the risk for SSI. Wound surveillance in the post-discharge period is necessary for correct estimation of SSI rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
74
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 24 publications
10
74
1
9
Order By: Relevance
“…P. aeruginosa were 100 % resistant to oxacillin, ceftibuten, tetracycline, and erythromycin. This is comparable with the rates reported by various authors [5,6,10,[25][26][27][28][29][30][31][32][33]. Thus, the investigation demonstrated that in the Ukrainian surgery hospitals the incidence rate of SSIs causal agents resistant to antimicrobial medicines is quite high.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…P. aeruginosa were 100 % resistant to oxacillin, ceftibuten, tetracycline, and erythromycin. This is comparable with the rates reported by various authors [5,6,10,[25][26][27][28][29][30][31][32][33]. Thus, the investigation demonstrated that in the Ukrainian surgery hospitals the incidence rate of SSIs causal agents resistant to antimicrobial medicines is quite high.…”
Section: Discussionsupporting
confidence: 80%
“…The distribution of various groups of microorganisms varies considerably [5][6][7][8][9][10][25][26][27][28][29]. This proves the necessity of carrying out microbiological monitoring in every surgery hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that cigarette smokers have increased cardiovascular disease 23 and a higher risk of recurrent myocardial infarction 24,25 . Studies in colorectal and abdominal surgery indicate that patients with congestive heart failure have a higher risk of developing surgical site infections 26,27 . Thus, we performed a series of stacked multiple regressions to adjust the weighted effect of smoking status, packs per decade, and comorbidities, given the potential for colinearity among confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that diabetes mellitus, smoking, operations lasting more than 3 hours, the absence of antibiotic prophylaxis, and a history of previous surgery were positive risk factors associated with a significant upsurge in SSIs. 87 SSIs comprise at least 14%-22.2% of all HCAIs for abdominal surgery [88][89][90] and often lead to extended hospitalization and higher antimicrobial costs. 71 The microorganisms generally involved in such SSIs include S. aureus, coagulasenegative Staphylococci and Enterococcus spp., and E. coli.…”
mentioning
confidence: 99%